Treatment with tPA Predicts Better Outcome Even if MCA Occlusion Persists. Issue 7 (October 2013) - Kablau, Micha; Alonso, Angelika; Hennerici, Michael G.; Fatar, Marc
Background and hypothesis: Functional improvement after middle cerebral artery ischaemia seems to depend on recanalization of large-vessel occlusion as early as possible. The only approved medical treatment for acute stroke is early IV tissue plasminogen activator administration. However, while some patients do not benefit from quick recanalization, others recover despite persistent middle cerebral artery occlusion. We wondered whether there are different effects of tissue plasminogen activator treatment on large artery and small artery reopening. Methods: We enrolled 55 acute stroke patients who showed persisting middle cerebral artery occlusion evidenced by transcranial colour-coded duplex ultrasonography in follow-up examination within 48 h postonset of middle cerebral artery stroke syndromes (mean 30·8 ± 5·4 h after admission). Twenty-two of 55 had been treated with tissue plasminogen activator and 33/55 had been treated without tissue plasminogen activator. We compared neurological (National Institutes of Health Stroke Scale) and functional (modified Rankin Scale) scores at baseline, after seven-days, and then after two-months. Risk factors, previous stroke prophylaxis, as well as clinical baseline characteristics were analysed to exclude significant differences between both groups. Results: Despite later admission to hospital (tissue plasminogen activator patients 1·6 ± 0·66 h vs. non-tissue plasminogen activator patients 7·4 ± 5·84 h; P < 0·001), there was no significant difference between both groups concerning demographic data, severity of symptoms on admission, risk factors, stroke prophylaxis, as well as basic laboratory values (international normalized ratio, leucocyte count, C-reactive protein) blood pressure and body temperature on admission. Irrespective of Doppler findings demonstrating persistent middle cerebral artery occlusion in all 55 patients, there was a significant neurological and functional improvement in tissue plasminogen activator patients compared to non-tissue plasminogen activator patients. Tissue plasminogen activator patients had a mean improvement on National Institutes of Health Stroke Scale within the first seven-days of 2·8 points, while non-tissue plasminogen activator patients deteriorated by 2·2 points ( P < 0·001). Concerning modified Rankin Scale tissue plasminogen activator-treated patients showed a mean improvement within the first seven-days of 0·5 points, while non-tissue plasminogen activator patients deteriorated by 0·3 points ( P = 0·019). A favourable overall short-term clinical course (i.e. improvement on National Institutes of Health Stroke Scale >3 points and/or modified Rankin Scale >1 point) was found in 36·4% of tissue plasminogen activator patients and in 6·1% of non-tissue plasminogen activator patients ( P = 0·0047). At two-months follow-up, patients still showed a median modified Rankin Scale of 4 points after tissue plasminogen activator treatment and 5 points after non-tissue plasminogen activator treatment ( P = 0·023). Conclusion: Although the prognosis of patients with persisting middle cerebral artery occlusion after tissue plasminogen activator administration is known to be poor, patients do better if treated with tissue plasminogen activator vs. those who could not be treated – mainly for late presentation. This may be due to sufficient small vascular territory recanalization despite persistence of large artery occlusion after tissue plasminogen activator treatment.